PERTUMBUHAN SISTEM HUKUM NASIONAL: SUATU ANALISIS HISTORIS DAN KONSEPTUAL - Rayhan Ananda Sonata; Sarah Faadiyah Akmal; Nella Tiara putri Pinem; Putri Amanda Shila (PT. Hasba Edukasi Mandiri, 2025)
Indonesia's national legal system developed through a long process influenced by historical heritage, political dynamics, social values, and advances in modern legal thought. This paper examines the development of the national legal system using two main perspectives: a historical approach and a conceptual approach. From a historical perspective, Indonesia's legal configuration was shaped by the application of customary law, the Dutch colonial legal system, religious legal norms, and the process of national law formation after independence. Meanwhile, conceptually, this development is related to efforts to rebuild a legal order based on Pancasila, the principles of the rule of law, and efforts to harmonize various sources of law. The findings of this study indicate that Indonesia's national legal system continues to undergo changes toward a more responsive, adaptive, and socially just system, although it still faces issues of legal integration, regulatory inconsistencies, and weak law enforcement effectiveness.